2016
DOI: 10.5455/msm.2016.28.416-419
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Urinary Isolates of Escherichia coli

Abstract: Objectives:The aim of this study was to examine the presence of antimicrobial resistance / susceptibility strains of Escherichia coli in inpatients and outpatients.Materials and methods:It is a retrospective study carried out at the Department of Microbiology, Parasitology and Virology Faculty of Medicine, University of Sarajevo. In cooperation with the Microbiological laboratory of the Cantonal Hospital Zenica and the Microbiological laboratory of the General Hospital Tesanj, 3863 urine samples were processed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 14 publications
3
21
1
Order By: Relevance
“…Some studies favor and some goes against the result of 85 our present study. [18,26,27] But less increasing resistance (from 0.7% to 0.9%) and higher susceptibility (>80%) in US support our report. [4,25] c. Ciprofloxacin: The quinolone derivative, Ciprofloxacin is used empirically not only in UTIs but also in various forms infections due to its safety profile and cheap in price.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Some studies favor and some goes against the result of 85 our present study. [18,26,27] But less increasing resistance (from 0.7% to 0.9%) and higher susceptibility (>80%) in US support our report. [4,25] c. Ciprofloxacin: The quinolone derivative, Ciprofloxacin is used empirically not only in UTIs but also in various forms infections due to its safety profile and cheap in price.…”
Section: Discussionsupporting
confidence: 88%
“…[15] It is well postulated that UTI is more common among the woman due to the closer alignment of urethra to the anus and shorter urethra which we have found in our present study at a ratio of 8:1.5. [16][17][18][19] Common risk factors causing UTIs are sexually active premenopausal women, use of spermicides for contraceptive, frequent change of sexual partners, age of the first UTI, maternal history of UTI, wearing tight undergarments, deferred voiding habit, pregnancy, DM and immunosuppression due to any cause. [20][21][22] So, reproductive age plays a vital role as a risk factor for developing UTI in both sex.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with many previous reports [ 30 , 40 42 ] showing that ESBL-producing E. coli isolates were more resistant to trimethoprim-sulphamethoxazole, ciprofloxacin, and third-generation cephalosporins compared to non-ESBL-producing E. coli , although this resistance did not affect imipenem. This increased resistance levels of ESBL-producing E. coli isolates to some front-line antibiotics such as cephalosporins, trimethoprim-sulphamethoxazole, and ciprofloxacin, could be ascribed to the inappropriate and excessive use of these agents in the empirical treatment of UTIs [ 43 ]. It has been shown that these antibiotics are commonly used for the treatment of UTIs worldwide [ 44 ], and the currently reported increase in resistance trends among uropathogens, primarily E. coli , has not only led to high rates of morbidity and mortality [ 45 ], but it has also complicated the management of UTIs [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by constant supervision and knowledge of the most common bacterial species as the etiologic agents of urinary tract infections, as well as their resistance profile (19). …”
Section: Discussionmentioning
confidence: 99%
“…It is essential to maintain the safety and feasibility of empirical therapy, as a strategy for managing urinary tract infections in female. This can be achieved by constant supervision and knowledge of the most common bacterial species as the etiologic agents of urinary tract infections, as well as their resistance profile ( 19 ).…”
Section: Discussionmentioning
confidence: 99%